2016
DOI: 10.1088/0953-2048/29/4/045009
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and superconducting properties of nanocarbon-doped internal Mg diffusion-processed MgB2wires fabricated using different boron powders

Abstract: MgB2/Nb/Monel monofilament wires were fabricated using four different boron powders by an internal Mg diffusion (IMD) process. The microstructure, morphology and the critical current density (Jc) of the used boron powders and the formative MgB2 layers were analyzed and compared. It was found that the purity and particle size of the boron powder influence the superconducting properties of MgB2 wires; further that the optimized heat-treatment condition also depends on the quality of the boron powder. The highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Purity and particle size of boron powder are identified as the main two factors [18][19][20]. A previous work of our group has shown that the boron powder purity has a more strong influence on the properties of MgB 2 wires than the particle size [21]. Additionally, the dispersion of dopants in the boron powder matrix is also quite critical, as the subsequent processing steps like cold working and heat treatment will not improve the dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…Purity and particle size of boron powder are identified as the main two factors [18][19][20]. A previous work of our group has shown that the boron powder purity has a more strong influence on the properties of MgB 2 wires than the particle size [21]. Additionally, the dispersion of dopants in the boron powder matrix is also quite critical, as the subsequent processing steps like cold working and heat treatment will not improve the dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…The MgB 2 bulk sample manufacturing process consists of a combination of the Internal Magnesium Diffusion (IMD) and the Powder-in-Closed-Tube (PiCT) techniques 26 , 27 . Samples prepared by IMD are typically characterized by high electrical connectivity 28 . The PiCT technique allows in turn achieving a high density of the reacted MgB 2 phase and a high reproducibility of the sample properties 27 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this study also first clarifies the direct relationship between the performance of the wire and its microstructure based on the hybrid microscopy of the SHPM and SEM. In fact, recent high-performance MgB 2 wires have been fabricated without SiC: C doping by other methods [40][41][42].…”
Section: Site-specific Microstructure Observationmentioning
confidence: 99%